Analisis Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU) dan Belanja Modal terhadap Tingkat Kemandirian Daerah (Studi Kasus Pada Kabupaten/Kota di Jawa Timur Periode 2010-2014) - Megariski, Hestu Pradipta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The main objective of the regional autonomy is an area in which financial independence is able ti finance all development needs to explore the potential of their respective regions to increase local revenue. Financial independence of this region can be measured by the ratio of local financial independence. The degree of independence of East Java province tends to increase every year and are in less position because the average is less tahn 20%. The level of financial independence this area can be describe the condition of the economy of a region.With a few variables have been determined, the study aims to : (1) know how to influence local revenue on the level of financial independence in East Java province, (2) know how to influence the general allocation fund on the level of local financial independence East Java Province, (2) determine how the effects of capital spending to the level of local financial indeppendence of local financial independence of East Java Province. The case study research in all counties and cities in East Java in 2010-2014. The analytical method used is the panel data regression. Result of the study using a fixed effect model showed that the local revenue and capital expenditure significant positive effect on the level of local financial independence while the general allocation fund also has significant effect and negative direction on the level of local financial independence in East Java.Key Words : Level of Regional Financial Independence, Local Revenue, General Allocation Fund, Capital Expenditure